Hepatoprotective Activity of Aralia racemosa L. and its Triterpenoid and Steroid Compounds against Paracetamol Induced Liver Injury in Albino Wistar Rat (Global Journal of Medical Research, 2017)
Objective: There exists a deficit of reliable hepatoprotective drugs in modern medicine to prevent and treat drug-induced liver damage. The root of Aralia racemosa L. belonging to family Araliaceae is pre-owned long established for their hepatoprotective effect. The prevailing research was accompained to identify and isolate the phytoconstituents of Aralia racemosa L. root methanolic extract (MEAR) for its hepatoprotective effect. Materials and Methods: The dried root of A. racemosa was extracted with methanol and partitioned between Petroleum ether, chloroform, ethyl acetate, and n-butanol. The organic layer was fractionated by various stationary phases and identified by using spectral analysis. MEAR (200 and 400 mg/kg, p.o.) and isolated compounds were assessed for its hepatoprotective activity in PCM-induced liver toxicity in Rats. The hepatoprotective activity was assessed from biochemical and histopathological studies. Results: Phytochemical investigation of the roots of Aralia racemosa L. (Araliaceae) afforded four known Phytoconstituents identified as Stigmasterol (1), ß-Sitosterol (2), Ursolic acid (3) and Oleanolic acid (4). The structures of those phytoconstituents have been elucidated based on spectral information analysis. Stigmasterol and Ursolic acid were isolated from this plant for the first time. The PCM intoxication leads to histological and biochemical deteriorations. The treatment with MEAR and the isolated compounds 1 to 4 significantly lowered the elevated levels of SGOT, SGPT, ALP, TB, as well as regressive the hepatic damage towards normal which further supports the hepatoprotective activity of MEAR. Conclusion: This result strongly supports that MEAR had a significant protective effect against Paracetamol (PCM) - induced liver injury due to Phytosterols i.e., Stigmasterol, ß- Sitosterol and Triterpenes i.e., Oleanolic Acid and Ursolic acid.
Keywords: hepatoprotective; ursolic acid; oleanolic acid; silymarin; aralia racemosa L; ?-sitosterol